Effect of Chick Weight, Geometric Mean Diameter and Sodium Level In Prestarter Diets (1 to 7 Days) on Broiler Perfomance up to 21 Days of Age - AML Ribeiro (Revista Brasileira de Ciência Avícola, 2004)
Seven hundred and twenty Ross 308 chicks were raised in a controlled environment room, distributed in a factorial design with 3 hatching chick weights (37, 40 and 44 g), 3 geometric mean diameter (GMD) (0.561; 0.783 and 0.997 mm) and 4 total sodium levels (Na) (0.12; 0.24; 0.36 and 0.48%) in the pre-starter diet (1 to 7 days). From 8 to 21 days (d) one single basal diet was used for all treatments. The thirty seven-gram chicks had the smallest yolk sack weight at 4d, smallest body weight (BW) and feed intake (FI) at 7d and 21d, but the same feed conversion (FC) than the other groups of hatching weight. Chicks receiving diet with intermediate GMD had the greatest BW and FI at 7d, but at 21d this effect was no longer seen. The diet with finest particle size resulted in birds with the smallest gizzard weight at 7d. The 0.12%Na diet was statistically different from the other Na levels, resulting in chicks at 7d with the worst FC and lowest body weights. At 21d, BW still was the lowest for this group of chicks. Birds with 0.48%Na produced more watery excreta and less dry matter in the carcass at 7d. Water consumption (C H2O) was influenced linearly by chick weight up to 0.36%Na level. In the 0.48%Na level, 40 and 44 g chicks had similar C H2O, which was different from 37-g chicks. For best performance, Na values were set from 0.31 to 0.48%. The three studied factors influenced quality of pre-starter diet and consequently chick performance.